حق الرد وحق التصحيح عبر الموقع الالكتروني في الصحافة الالكترونية وخدمة السمعي البصري عبر الانترنت دراسة تحليلية للمرسوم التنفيذي رقم 20-332.) Right of reply and right of correction via the website in electronic journm and audiovisual service on the Intern - بن احمد الطاهر (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
لقد ضمن المشرع الجزائري حق الرد وحق التصحيح للأشخاص المتضررين ماديا و معنويا من جراء نشر مقال عبر الصحافة الالكترونية أو خدمة السمعي البصري عبر الانترنت ،لذلك جاءت هذه الدراسة لتبين كيفية ممارسة هذه الحقوق عبر الموقع الالكتروني، من خلال تحليل نصوص المرسوم التنفيذي رقم 20-332، وهو الإطار التشريعي للإعلام الالكتروني في الجزائر. وقد توصلت إلى تحديد من له ممارسة هذا الحق، و أي شخص طبيعي أو معنوي يتم ذكره اسميا أو تحديده ضمنيا له حق الرد أو التصحيح، وأن سريان هذا الحق يبدأ من أول يوم للنشر وذلك وفق شروط شكلية وأخرى موضوعية حددها القانون . Abstract: The Algerian legislator has guaranteed the right of reply and the right of correction to people who are financially or morally damaged by publishing an article through the electronic press or audio-visual service via the Internet. Therefore, this study came to show how to exercise these rights through the website by analyzing the texts of Executive Decree No. 20-332, which is The legislative framework for electronic media in Algeria. And it concluded who is able to exercise this right, and that any normal moral person that is mentioned by name or implicitly has the right to correct or the right to reply, And that the validity of this right starts from the first day of publication, according to formal or objective conditions defined by law.